Benefits of Minimal Invasive Surgery for Inguinal Hernia Repair in Bangladesh - Saha, Pankaj Kumar; Roy, Ratna Rani; Yusuf, Md Abdullah (Journal of Monno Medical College, 2025)
Inguinal hernia is a common condition where intestinal or fatty tissue protrudes through a weak spot in the abdominal wall, often causing discomfort and restricted movement. Traditional open surgery has been the standard treatment, but minimally invasive surgery (MIS), including laparoscopic and robotic-assisted techniques, has gained popularity due to its advantages. These advanced procedures involve small incisions, specialized instruments, and a camera for precise hernia repair, leading to faster recovery, reduced pain, and lower complication risks. Laparoscopic surgery uses a camera and small tools to place a reinforcing mesh, while robotic-assisted surgery provides enhanced precision through robotic arms controlled by the surgeon. MIS results in less postoperative pain, quicker recovery, and a lower risk of infections, hematomas, and nerve damage. Additionally, it leaves minimal scarring and allows for the simultaneous repair of bilateral hernias. Additionally, it requires highly skilled surgeons and has higher initial costs. Despite these limitations, MIS is becoming the preferred approach for inguinal hernia repair, offering better patient outcomes and contributing to improved healthcare in Bangladesh. Journal of Monno Medical College December, 2024;10 (2):107-109